Heterogeneity of genetic architecture of body size traits in a free‐living population - Camillo Bérénos; Philip A. Ellis; Jill G. Pilkington; S. Hong Lee; Jake Gratten; Josephine M. Pemberton (Molecular Ecology, 2015)
Knowledge of the underlying genetic architecture of quantitative traits could aid in understanding how they evolve. In wild populations, it is still largely unknown whether complex traits are polygenic or influenced by few loci with major effect, due to often small sample sizes and low resolution of marker panels. Here, we examine the genetic architecture of five adult body size traits in a free‐living population of S oay sheep on S t K ilda using 37 037 polymorphic SNP s. Two traits (jaw and weight) show classical signs of a polygenic trait: the proportion of variance explained by a chromosome was proportional to its length, multiple chromosomes and genomic regions explained significant amounts of phenotypic variance, but no SNP s were associated with trait variance when using GWAS . In comparison, genetic variance for leg length traits (foreleg, hindleg and metacarpal) was disproportionately explained by two SNP s on chromosomes 16 (s23172.1) and 19 (s74894.1), which each explained >10% of the additive genetic variance. After controlling for environmental differences, females heterozygous for s74894.1 produced more lambs and recruits during their lifetime than females homozygous for the common allele conferring long legs. We also demonstrate that alleles conferring shorter legs have likely entered the population through a historic admixture event with the D unface sheep. In summary, we show that different proxies for body size can have very different genetic architecture and that dense SNP helps in understanding both the mode of selection and the evolutionary history at loci underlying quantitative traits in natural populations.

Erratum to: Gene mapping in the wild with SNPs: guidelines and future directions - Jon Slate; Jake Gratten; Dario Beraldi; Jessica Stapley; Matt Hale; Josephine M. Pemberton (Genetica, 2010)

Gene mapping in the wild with SNPs: guidelines and future directions - Jon Slate; Jake Gratten; Dario Beraldi; Jessica Stapley; Matt Hale; Josephine M. Pemberton (Genetica, 2009)